Evolutionary dynamics of plastomes in coscinodiscophycean diatoms revealed by comparative genomics - Liu, Feng; Wang, Yichao; Huang, Hailong; Chen, Nansheng (Frontiers in Microbiology, 2023)
To understand the evolution of coscinodiscophycean diatoms, plastome sequences of six coscinodiscophycean diatom species were constructed and analyzed in this study, doubling the number of constructed plastome sequences in Coscinodiscophyceae (radial centrics). The platome sizes varied substantially in Coscinodiscophyceae, ranging from 119.1 kb of Actinocyclus subtilis to 135.8 kb of Stephanopyxis turris. Plastomes in Paraliales and Stephanopyxales tended to be larger than those in Rhizosoleniales and Coscinodiacales, which were due to the expansion of the inverted repeats (IRs) and to the marked increase of the large single copy (LSC). Phylogenomic analysis indicated that Paralia and Stephanopyxis clustered tightly to form the Paraliales-Stephanopyxales complex, which was sister to the Rhizosoleniales-Coscinodiscales complex. The divergence time between Paraliales and Stephanopyxales was estimated at 85 MYA in the middle Upper Cretaceous, indicating that Paraliales and Stephanopyxales appeared later than Coscinodiacales and Rhizosoleniales according to their phylogenetic relationships. Frequent losses of housekeeping protein-coding genes (PCGs) were observed in these coscinodiscophycean plastomes, indicating that diatom plastomes showed an ongoing reduction in gene content during evolution. Two acpP genes (acpP1 and acpP2) detected in diatom plastomes were found to be originated from an early gene duplication event occurred in the common progenitor after diatom emergence, rather than multiple independent gene duplications occurring in different lineages of diatoms. The IRs in Stephanopyxis turris and Rhizosolenia fallax-imbricata exhibited a similar trend of large expansion to the small single copy (SSC) and slightly small contraction from the LSC, which eventually led to the conspicuous increase in IR size. Gene order was highly conserved in Coscinodiacales, while multiple rearrangements were observed in Rhizosoleniales and between Paraliales and Stephanopyxales. Our results greatly expanded the phylogenetic breadth in Coscinodiscophyceae and gained novel insights into the evolution of plastomes in diatoms.